2022
DOI: 10.3389/fnut.2022.991907
|View full text |Cite
|
Sign up to set email alerts
|

Association between dietary inflammatory index and metabolic syndrome: Analysis of the NHANES 2005–2016

Abstract: ObjectiveMetabolic syndrome (MetS) is a global problem that increasingly violates human health and quality of life. We explored the relationship between dietary inflammatory potential represented by dietary inflammatory index (DII) and the occurrence of MetS to provid data support for the prevention of it through dietary structure intervention.MethodsThe data was come from National Health and Nutrition Examination Survey 2007–2018, including demographic, dietary, questionnaire variables and laboratory indicato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 56 publications
1
8
0
Order By: Relevance
“…Meeting these targets may help prevent development of individual MetS components including central obesity, hypertension, dyslipidemia and hyperglycemia. In alignment with our findings, previous studies have linked higher HEI scores to lower prevalence of obesity, diabetes, hypertension and dyslipidemia ( 6 9 ). Two separate studies, one focusing on Korean adults and the other on Iranian adults, have also reported the associations between HEI scores and MetS risk ( 19 , 20 ).…”
Section: Discussionsupporting
confidence: 93%
“…Meeting these targets may help prevent development of individual MetS components including central obesity, hypertension, dyslipidemia and hyperglycemia. In alignment with our findings, previous studies have linked higher HEI scores to lower prevalence of obesity, diabetes, hypertension and dyslipidemia ( 6 9 ). Two separate studies, one focusing on Korean adults and the other on Iranian adults, have also reported the associations between HEI scores and MetS risk ( 19 , 20 ).…”
Section: Discussionsupporting
confidence: 93%
“…The DII, which illustrates the inflammatory effects of daily diets, relates to the possibility of a variety of harmful health outcomes (19,(43)(44)(45). Zhang et al (46) reported that DII is related to the development of MetS and has a significant impact on blood pressure, lipid levels, and BMI. Wu et al (47) investigated the connection between DII and coronary heart disease, indicating that patients with coronary heart disease had considerably higher DII values compared to those without coronary heart disease.…”
Section: Discussionmentioning
confidence: 99%
“…Participants were provided with standardized questionnaires to collect sociodemographic and lifestyle information. Based on previous studies, we included covariates for adverse cardiometabolic health risk factors, which included low socioeconomic status [ 31 ], smoking status [ 32 ], alcohol consumption status [ 32 ], history of cancer [ 33 ], exercise status [ 34 ], and family history of diabetes [ 4 ]. We included sex (male or female), age continuous or categorical variables (18–39, 40–59, or ≥ 60 years), race/ethnicity (non-Hispanic black, other Hispanic, non-Hispanic white, or other races), marital status categorized as (married, living alone, or divorced), educational attainment (less than high school, high school, and more than high school), PIR (categorized as < 1, 1–2, 2–4, and > 4), and smoking status was categorized as never smoked (< 100 cigarettes before the survey), ever smoked (> 100 cigarettes before the survey but quit before the survey), and current (> 100 cigarettes before the survey and smoked during the survey) as well as self-reported history of cancer, family history of diabetes, and substance use.…”
Section: Methodsmentioning
confidence: 99%
“…Numerous studies have demonstrated a notable correlation between MetS and both systemic inflammation and immune response. The prevailing perspective posits that MetS originates from excessive obesity [ 4 ], which is characterized by mild chronic inflammation. Inflammatory factors, secreted by adipose tissue, contribute to the development of metabolic disorders by instigating a systemic inflammatory response [ 5 ].…”
Section: Introductionmentioning
confidence: 99%